Undergraduate Students’ Utilisation of Digital Information Resources at the University of Lagos, Nigeria: The Role of Digital Literacy - Yila, Umar Musa (University of Dar es Salaam Library Journal, 2024)
This paper investigates the relationship between digital literacy and digital information resource utilisation among undergraduate students at the University of Lagos. The specific objectives of the study were to determine the level of digital literacy skills of undergraduate students at the University of Lagos; examine the extent of utilisation of digital information resources among undergraduates at the University of Lagos; and, finally, examine the relationship between digital literacy skills and utilisation of digital information resources among the undergraduates in the University of Lagos. The study used two research questions to achieve objectives one and two and tested a hypothesis to examine the relationship between digital literacy skills and the utilisation of digital information resources. The survey research design was adopted to select two hundred ten (210) 400-level undergraduate students across the 12 faculties of the University of Lagos using the Multi-stage Sampling Technique. The questionnaire was used to collect data from the respondents. Data collected for the research questions were analysed using frequency counts, percentages, and means whereas linear regression and multiple regression were used to test the hypotheses of the study. The study found that the level of digital literacy skills of the respondents is very high. The extent to which they use digital information resources available to them is also very low. The results also revealed that there is a positive linear relationship between digital literacy skills and the use of digital information resources by undergraduate students at the University of Lagos. The study found a positive linear relationship between digital literacy skills and the use of digital resources by undergraduate students at the University of Lagos. Impliedly, even though undergraduate students at the University of Lagos possess high digital literacy skills, their utilisation of digital information resources remains low, highlighting the need for targeted digital literacy training to enhance effective resource usage. Keywords: Digital skills, use of digital information resources, undergraduate students, University of Lagos, library. https://dx.doi.org/10.4314/udslj.v19i2.10